Establishment of a Supervisory Institution as Effort Fulfillment of Children's Rights Due To Divorce - Ummu Salamah; Tahir Luth; Rachmi Sulistyarini; Dhiana Puspitawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The responsibility of parents towards fulfilling children's rights must still be carried out even though both parents have divorced. In the Constitutional Marriage it is explained that a father is responsible for all the rights to life for his children, but often the father is negligent in fulfilling his obligations even though there has been a judge's decision in court. Basically in court, actually the implementation of a request in fulfilling the child's maintenance rights can be done if the father is negligent, but the implementation is not easy. This study will examine what are the juridical obstacles to fulfilling children's rights as a result of divorce and how to fulfill children's livelihood rights in the future. The purpose of this study is to describe efforts to fulfill children's livelihood rights as a result of divorce. This research is a normative legal research with a literature study approach, a case approach, and a comparison of efforts to fulfill children's rights to a just life. The results of the research in this description are that it is very necessary to have a supervisory institution that will oversee the level of compliance of fathers in fulfilling their children's right to life due to divorce.